(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Diabetes mellitus is a multifactorial metabolic disorder associated with the diabetes related vascular diseases. Oxidative stress along with inflammation is the Key factor leading to diabetic complications. Present study was designed to investigate the protective role of diosgenin, a steroidal saponin, in diabetes induced early kidney injury and oxidative stress markers and histopathological changes in kidney of diabetic rats, induced by single intra-peritoneal injection of streptozotocin (55 mg/kg weight (b.w.). After 72 hrs, experimental rats received diosgenin at different doses (10, 20 and 40 mg/kg b.w.) once daily for four weeks. At the end of the experiment, diabetic rats showed a significant increase in the levels of plasma glucose, glycosylated hemoglobin with a significant decrease in insulin and total hemoglobin. The activities of antioxidant enzymes such as superoxide dismutase, catalase, reduced glutathione, and the levels of reduced glutathione were decreased while increases in the levels of lipid peroxidation markers were observed in kidney tissues of diabetic rats. Oral administration of diosgenin to diabetic rats considerably shrivelled the plasma glucose and exaggerated the endocrine level supported a dose dependent manner. Diosgenin at a dose of 40 mg/kg b.w. was more pronounced effect than the other two doses and used for further studies. All the manifestations observed in diabetic rats were significantly reversed to near normal at a dose of 40 mg/kg b.w. of diosgenin. These findings recommend that diosgenin may have a helpful role against excretory organ harm evoked by aerobic stress within the diabetic state.